The Meaning Of Halal Tourism Reviewing From Social Semiotics - Tetra Tianiafi; Yohannes Don Bosco Doho; Al Ghazali Al Ghazali (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Discourse on halal tourism appears rife in a number of communication channels. The flow of the journey of the presence of the word halal tourism is influenced by actors who play an important role in the development of tourism products in Indonesia. This of course can be traced based on the track record of reporting on halal tourism discourse that was presented in the past ten years from 2012 to 2021. This search can easily be traced through the track record of digital communication media news. Opinions of the pros and cons related to the existence of halal tourism continue. The role of actors, actions, modalities, genres, styles that play an important role in the meaning of halal tourism. Leuween's social semiotics is present in an effort to understand the debate about the existence of halal tourism in Indonesia. The deepening and exploration of the concepts of semiotic resources, semiotic inventories, semiotic change, semiotic function and semiotic rules is expected to provide an understanding of the true meaning of halal tourism. The qualitative research method used in the interpretation of social semiotics is presented through the identification of a number of artifacts found in a number of news broadcasts. This difference in meaning has resulted in not maximally utilizing the opportunities offered by reports of profits in global transactions for the global halal tourism business, which can be obtained by a number of tourism stakeholders in Indonesia.